The effect of limb position on measured values of vastus lateralis muscle morphology using B Mode ultrasound. Issue 6 (6th August 2021) - Jacob, Isobel; Jones, Gareth; Francis, Peter; Johnson, Mark I.
Abstract : It is not known whether different leg positions influence measurements of muscle thickness, pennation angle, and fascicle length. The primary aim of this study was to determine whether extension or flexion of the leg affected measurements of muscle morphology in the vastus lateralis. Thirty‐two male professional football players participated in the study. B mode ultrasound (LOGIQ e, GE Healthcare, United States) was used to capture images of the vastus lateralis from the dominant leg of each participant when their leg was (a) extended at the knee and (b) flexed at the knee by 90 degrees. Data were analyzed using paired t tests. Muscle thickness and pennation angle were greater when the leg was extended (2.43 ± 0.18cm vs 2.36 ± 0.17 cm; t(31) = 2.76, P < .010; 18.47 ± 1.18° vs 16.87 ± 1.14°; t(31) = 7.59, P < .001, respectively). Fascicle length was greater when the leg was in flexion (9.87 ± 0.53 cm, flexion vs 9.04 ± 0.92 cm; t(31) = −7.652, P < .001). The intra‐rater reliability of the investigator was assessed using a 2‐way mixed‐effects model. In conclusion, leg position affects measurements of muscle morphology in vastus lateralis; this should be considered when comparing findings between studies.